Teachers' Difficulties in Teaching Mathematics for Grade XI: Case Study in Nias Adventist High School - Zebua, Julta Erniat (Nashir Al-Kutub Indonesia, 2024)
This study aimed to identify and analyze the difficulties experienced by teachers in teaching Mathematics to XI-grade students. The research used a qualitative approach to examine the challenges faced by teachers in teaching Mathematics to IX-grade students. The participants in this study included two mathematics teachers and 32 eighth-grade students. The results of the study showed that teachers faced difficulties in several aspects, including a lack of understanding of basic concepts, difficulties in applying concepts, lack of motivation, lack of parental support, and insufficient skills in using mathematical tools. To address these challenges, teachers implemented various effective teaching strategies, such as project-based learning, computer-based learning, and group-based learning. These strategies helped students better understand mathematical concepts and increased their motivation to learn mathematics. It was also important for teachers to show the connection between mathematics and students' daily lives, so they could see the relevance of mathematics in their lives. Teachers sought assistance and developed their skills in information technology to improve the quality of Mathematics instruction. The importance of teaching mathematics lay in the way teachers engaged students, ensuring they were motivated and interested in learning mathematics by linking the material to real-life situations, creating interactive and engaging lessons, and building positive relationships with students. Teachers adopted innovative strategies such as project-based learning, computer-based learning, and real-life applications to enhance students’ understanding and motivation in mathematics. Additionally, professional development programs and stronger collaboration with parents were essential to effectively address teaching challenges.